2020
DOI: 10.1097/md.0000000000019890
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran-induced esophagitis

Abstract: Rationale: Dabigatran is an anticoagulant medication that has been widely used to prevent strokes caused by atrial fibrillation, deep vein thrombosis, and pulmonary embolism. However, the potential adverse effect of dabigatran of gastrointestinal mucosal injury is often neglected, and even induces esophagitis. Patient concerns: A 77-year-old woman was admitted to the hospital with symptoms of progressive retrosternal pain, upper abdominal discomfort, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Note that no significant association was found between platelet count or Child–Pugh Grade and major bleeding. However, some case reports have found that dabigatran is associated with exfoliative esophagitis and esophageal ulcer [ 46 48 ]. Toyo et al displayed that 19 (20.9%) of the 91 patients receiving dabigatran showed esophagitis in a retrospective study [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that no significant association was found between platelet count or Child–Pugh Grade and major bleeding. However, some case reports have found that dabigatran is associated with exfoliative esophagitis and esophageal ulcer [ 46 48 ]. Toyo et al displayed that 19 (20.9%) of the 91 patients receiving dabigatran showed esophagitis in a retrospective study [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 Previous reports showed that DIE usually develops shortly or approximately one year after dabigatran initiation. 2 , 3 This is an extremely rare case in which DIE became apparent eight years after its commencement. If a patient taking dabigatran presents with chest or abdominal symptoms, clinicians should consider that DIE may be the cause regardless of its start date.…”
Section: To the Editormentioning
confidence: 95%
“… 2 DIE may be asymptomatic or present along with one or more of the following symptoms: chest pain, dysphagia, epigastralgia, and heartburn. 3 DIE presents with the characteristic endoscopic finding of longitudinal sloughing of the epithelium in the middle to the distal esophagus, which is the key to its diagnosis. 2 Treatment options include instructing patients how to take dabigatran to avoid lodging in the esophagus (i.e., taking dabigatran with plenty of water and maintaining an upright position for 30 minutes or more after taking it) and switching to another DOAC.…”
Section: To the Editormentioning
confidence: 99%
“…Dabigatran-associated esophagitis (DAE) has been reported increasingly recently in the literature with conflicting findings. 1–5 Toya et al 1 reported that nearly 20% of patients who ingested dabigatran had evidence of esophagitis on endoscopy. On the other hand, Tajima et al 2 reported that DAE prevalence was nearly 9%.…”
mentioning
confidence: 99%